2016
DOI: 10.1089/acm.2016.0070
|View full text |Cite
|
Sign up to set email alerts
|

Memory Impairment, Dementia, and Alzheimer's Disease in Classical and Contemporary Traditional Chinese Medicine

Abstract: Memory impairment in older age was a recognized condition in the classical literature. Many of the traditional medicines frequently used as ingredients in classical formulas for memory impairment consistent with clinical features of AD remain in contemporary use, and experimental studies suggest biological activities relevant to AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…e 10 most frequently used herbs in the formulae for age-related memory disorders found in the previous study were all included in our list of the top 20 frequently used herbs. Another previous study identified five herbal species for memory impairment based on the Encyclopedia of Traditional Chinese Medicine database, including Poria cocos, Polygala tenuifolia, Rehmannia glutinosa, Panax ginseng, and Acorus species, which were all included in our list [41]. Also, a dendrogram of hierarchical clustering of herbs in a previous study found three clusters of herbs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…e 10 most frequently used herbs in the formulae for age-related memory disorders found in the previous study were all included in our list of the top 20 frequently used herbs. Another previous study identified five herbal species for memory impairment based on the Encyclopedia of Traditional Chinese Medicine database, including Poria cocos, Polygala tenuifolia, Rehmannia glutinosa, Panax ginseng, and Acorus species, which were all included in our list [41]. Also, a dendrogram of hierarchical clustering of herbs in a previous study found three clusters of herbs.…”
Section: Discussionmentioning
confidence: 95%
“…e blue nodes were mainly composed of tonifying-kidney herbs, whereas the green and purple nodes seem to be calming-liver herbs. 6 Evidence-Based Complementary and Alternative Medicine [41] and reported to have a potential of neuroprotective effect and improved cognitive function [42,43]. Among the individual herbs for memory impairment, Acori Graminei Rhizoma is known to have a protective effect on cognitive impairment in animal studies [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine believes that the main function of the lung is governing Qi to control respiration, as well as governing water, which connects the vessels and plays a role in dispersing and descending energy (May et al 2016). The kidney houses the essence.…”
Section: Discussionmentioning
confidence: 99%
“…is an example of traditional Chinese herbal medicine (TCM). There are other examples of TCM, such as Gingko biloba and Panax ginseng providing notable memory improvement when synergistically paired together [5]. The non-alkaloid classes of ACHEI of significance are flavonoids, phenolics and terpenoids, which are also known as isoprenoids.…”
Section: Review Articlementioning
confidence: 99%